Survey instrument for measuring level of preparedness amongst healthcare personnel in radiation emergency - Salleh, Siti Hasliah; Mohamed Yusof, Nor Ashikin; Ismail, Fadillah (Akademia Baru, 2021)
Drills and exercises are globally practiced to investigate the level of preparedness towards disaster events. However, these activities are rarely conducted because they require substantial investment, specifically to budget and time. A self-reported survey may serve as an alternative approach, although it may not be as effective as drills and exercises. As part of the survey development process, this article discusses preliminary validation of a survey instrument to measure the level of preparedness towards radiation emergency amongst healthcare personnel. Prior to this validation process, extensive literature reviews pointed out that the instrument consists of three constructs of preparedness, namely readiness, willingness, and ability. A total of seven subject matter experts were invited to judge the contents for verification purposes. Randolph Kappa analysis was then conducted to analyse their judgment to allow irrelevant items to be filtered from the rest prior to any improvements. Initially, the survey instrument consisted of 69 items; however, the analysis omitted 16 of them. The following values for each preparedness construct were: Readiness (0.77), Willingness (0.70), and Ability (0.73). These findings indicate that contents of the instrument are valid. Further analysis should be fulfilled to complete validation process to ensure its practicality prior to using it as an evaluation tool.